KEWENANGAN PERUSAHAAN DAERAH AIR MINUM ATAS PENGELOLAAN AIR BERSIH DI KABUPATEN BADUNG - I Made Banda Prawira; I Ketut Sudiarta; Cokorda Dalem Dahana (Kertha Negara : Journal Ilmu Hukum, 2014)
Regional Water Company (PDAM) of Badung Regency has the authority andresponsibility for water resource management, including regulating, deciding andproviding licenses for provision of supply, use and cultivating of water resources. Theauthority of Regional Water Company (PDAM) of Badung in providing generalservice creates an opportunity which possibly causes disputes to occur betweenRegional Water Company (PDAM) as the party having authority to water resourceand community as the customers. In relation to such matter, this paper discusses twoproblems: 1. The authority of Regional Water Company of Badung Regency fordrinking water management in Badung Regency; 2. The legal liability of RegionalWater Company (PDAM) of Badung Regency, in the event of disputes arise with service users of Regional Water Company. The method applied is normative researchmethods.The conclusions obtained are: 1. The Regional Water Company (PDAM) of BadungRegency in implementing its authority on water supply management requiresagreement or power of attorney from the chief of the region through supervisingboard especially in determining rate; 2. In the event of a dispute arises, the settlementis prioritized through non litigation procedures, litigation action through district court.